1999
DOI: 10.1071/sb98030
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers and karyotypes in the Australian Gnaphalieae and Plucheeae (Asteraceae)

Abstract: Chromosome number determinations from 152 collections representing 42 genera and 106 species of the Australian Gnaphalieae and Plucheeae are reported. The chromosome numbers of 75 of these species have not been previously counted or differ from those previously reported for species. Chromosome numbers have been documented for the first time for 14 genera: Argyroglottis (n = 12), Cephalosorus (2n = 24), Decazesia (n = 14), Dielitzia (2n = 26), Eriochlamys (n = 14), Erymophyllum (n = 11 and 14), Gilruthia (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
38
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 12 publications
14
38
1
Order By: Relevance
“…In some cases, the karyotypes of Asteraceae, such as those belonging to the Gnaphalieae group (Watanabe et al, 1999b), can vary considerably in number, from 2n = 6 in Podolepis to 2n = 120 in Craspedia, and in symmetry, from unimodal in Podotheca to bimodal in Schoenia. Thus, the karyotype differences observed among Crepis japonica, Galinsoga parviflora and Chaptalia nutans appear to be common in the Asteraceae family.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the karyotypes of Asteraceae, such as those belonging to the Gnaphalieae group (Watanabe et al, 1999b), can vary considerably in number, from 2n = 6 in Podolepis to 2n = 120 in Craspedia, and in symmetry, from unimodal in Podotheca to bimodal in Schoenia. Thus, the karyotype differences observed among Crepis japonica, Galinsoga parviflora and Chaptalia nutans appear to be common in the Asteraceae family.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an important compilation is also available for Paraguay where almost 313 species of its fl ora have been citogenetically studied (Molero et al 2001). For other zones of South America (Central and Eastern Brazil) and Oceanía (Australia, Tasmania) despite the extensive studies on cytogenetic of plants, statistical estimations on the total number of examined species are not available (Jackson 1958, Smith-White 1959, Coleman 1982, Carvalheira et al 1991, Watanabe et al 1999, Forni-Martins & Martins 2000.…”
Section: Prospectsmentioning
confidence: 99%
“…Most genera of the Gnaphalieae have chromosome numbers that are multiples of 7 (Merxmüller et al 1977;Anderberg 1994;Watanabe et al 1999). However, n = 14 or 2n = 28 is the most frequent number in the tribe and Watanabe et al (1999) suggested x = 14 as the possible base number of the tribe.…”
Section: Discussionmentioning
confidence: 99%
“…However, n = 14 or 2n = 28 is the most frequent number in the tribe and Watanabe et al (1999) suggested x = 14 as the possible base number of the tribe. In Leontopodium, the chromosome number were reported as n = 12, 14 or 2n = 26, 48, 49, 52, 73 (Siljak 1977;Krogulevich 1978;Murin and Paclova 1979;Zhukova 1980;Krasnikova et al 1984;Nishikawa 1985;Vir Jee and Kachroo 1985;Khatoon and Ali 1988), and our results are 2n = 24, 28, 48, 52 and 72.…”
Section: Discussionmentioning
confidence: 99%